From classical democracy to liberal democracy: Definitions, types and paradigms - Taheri Mohammed Hanif; Afrough Emad (Kom: Časopis za Religijske Nauke)
This analytical-descriptive paper is written to re-examine and to study "democracy" critically, especially emphasizing "liberal democracy" as an attractive and acceptable concept in the system of political science field. Democracy has a long enough historical background and has undergone many historical transitions, transformations and developments. The academicians have verified different meanings for democracy, which have led to different definitions, types and paradigms for this terminology. Typology of democracy is the result of different theories, approaches, and attitudes toward it. Democracy, both in its classical and modern (liberal democracy) form, has some principles and indicators. Socio-political freedoms, equality of citizens in rights and privileges, regular holding of elections according to the law, establishment of government based on votes and separation of powers are the most important principles of democracy in its various forms. However, implementation of democracy depends on some conditions, but despite some defects and serious criticisms, it has some advantages and values which have caused it to be preferred over other methods of political orders. Democracy, as a method and structure of governance, is still an unfinished project that requires rethinking and deep considerations. Thus, the fluid and flexible concept and definition of democracy is compatible with different cultures, religions and societies, and, on this basis, we can talk about "Islamic democracy" and we can favour this vision as the findings of this research.